Efficacy of thoracic endovascular stent repair for chronic type B aortic dissection with aneurysmal degeneration - Scali, Salvatore T. (2013)
BACKGROUND: The Food and Drug Administration has approved devices for endovascular management of thoracic endovascular aortic aneurysm repair (TEVAR); however, limited data exist describing the outcomes of TEVAR for aneurysms attributable to chronic type B aortic dissection (cTBAD). This study was undertaken to determine the results of endovascular treatment of cTBAD with aneurysmal degeneration. METHODS: A retrospective analysis of all patients treated for cTBAD with aneurysmal degeneration at the University of Florida from 2004 to 2011 was performed. Computed tomograms with centerline reconstruction were analyzed to determine change in aortic diameter, relative proportions of aortic treatment lengths, and false lumen perfusion status. Reintervention and mortality were estimated using life-tables. Cox regression analysis was completed to predict mortality. RESULTS: Eighty patients underwent TEVAR for aneurysm due to cTBAD (mean age [± standard deviation], 60 ± 13 years [male, 87.5%; n = 70]; median follow-up, 26 [range, 1–74] months). Median time from diagnosis of TBAD to TEVAR was 16 (range, 1–72) months. Prior aortic root/arch replacement had been performed in 29% (n = 23) at a median interval of 28.5 (range, 0.5–312) months. Mean preoperative aneurysm diameter was 62.0 ± 9.9 mm. In 75% (n = 60) of cases, coverage was proximal to zone 3, and 24% (n = 19) underwent carotid-subclavian bypass or other arch debranching procedure. Spinal drains were used in 78% (pre-op 71%, n = 57; post-op 6%, n = 5). Length of stay was 6.5 ± 4.7 days with a composite morbidity of 26% and in-hospital mortality of 2.5% (n = 2). Overall neurologic event rate was 17% (spinal cord ischemia 10% [n = 8], with a permanent deficit observed in 6.2% [n = 5]; stroke 7.5%). Aneurysm diameter reduced or stabilized in 65%. The false lumen thrombosed completely within the thoracic aorta in 52%, and reintervention within the treated aortic segment was required in 16% (n = 13). One- and 3-year freedom from reintervention (with 95% confidence interval [CI]) was 80% (range, 68%–88%) and 70% (range, 57%–80%), respectively. Survival at 1 and 5 years was 89% (range, 80%–94%) and 70% (range, 55%–81%) and was not significantly different among patients requiring reintervention or experiencing favorable aortic remodeling. Multivariable analysis identified coronary artery disease (hazard ratio [HR], 6.4; 95% CI, 2.3–17.7; P < .005), prior infrarenal aortic surgery (HR, 8.6; 95% CI, 2.3–31.7; P = .001), and congestive heart failure (HR, 11.9; 95% CI, 1.9–73.8; P = .008) as independent risk factors for mortality. Hyperlipidemia was found to be protective (HR, 0.2; 95% CI, 0.05–0.6; P = .004). No significant difference in predictors of mortality were found between patients who underwent reintervention vs those who did not (P = .2). CONCLUSIONS: TEVAR for cTBAD with aneurysmal degeneration can be performed safely but spinal cord ischemia rates may be higher than previously reported. Liberal use of procedural adjuncts to reduce this complication, such as spinal drainage, is recommended. Reintervention is common, but long-term survival does not appear to be impacted by remediation.